2009
DOI: 10.4067/s0717-75182009000100006
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización De Queso Chanco Enriquecido Con Suero Lácteo en Polvo

Abstract: The influence by the addition of whey proteins on the biochemical changes in Chanco cheese ripening was evaluated. 4 treatments were set up: TC(control), and T1, T2 and T3 adding milk whey powder at 2, 4, 6% (m/m) respectively using a factorial design 3 x 4 (4 treatments by 3 repetitions). In pH control, humidity, fat, total solids, proteins, ashes and salt at 0, 14, 28 and 42 days, standardized methods were used: IDF-FIL, AOAC and Chilean guidelines. Color by colorimeter Color test LFM1, water activity by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…This could be due to the ripening period of 15 days, resulting in lower water lost. A longer ripening period of 21 days could cause a higher water loss in this cheese (Arteaga et al, 2009). There were no significant differences in the other parameters of cheese composition (P > 0.05), which could be attributed to the initial milk composition.…”
Section: Composition Of Chanco Cheesementioning
confidence: 72%
See 2 more Smart Citations
“…This could be due to the ripening period of 15 days, resulting in lower water lost. A longer ripening period of 21 days could cause a higher water loss in this cheese (Arteaga et al, 2009). There were no significant differences in the other parameters of cheese composition (P > 0.05), which could be attributed to the initial milk composition.…”
Section: Composition Of Chanco Cheesementioning
confidence: 72%
“…There were no significant differences in the other parameters of cheese composition (P > 0.05), which could be attributed to the initial milk composition. Arteaga et al (2009) reported higher protein and lipid contents (22.9% and 27.2%, respectively), and similar water content (54.3%) in commercial Chanco cheese at 14 days of ripening.…”
Section: Composition Of Chanco Cheesementioning
confidence: 81%
See 1 more Smart Citation
“…El agregado de suero lácteo no sólo aumenta rendimientos en los productos, sino que además se obtienen beneficios en la promoción de salud al enriquecer los productos con una gamma de componentes con alta funcionalidad fisiológica como son las proteínas del suero, algunos péptidos (glicomacropéptido), calcio, etc., dando además, un alto valor agregado a un producto de bajo costo derivado del propio procesamiento de quesos (Brito et al, 2002b;Playne et al, 2003;Arteaga, et al, 2009;) Los concentrados proteicos de leche, también permiten potenciar los productos lácteos, tanto aquellos en base a caseína como los de proteínas del suero, debido al contenido (ó potencial desarrollo) de varios componentes con actividad biológica, particularmente de los llamados péptidos bioactivos, que por lo general rebasan los índices de funcionalidad regular de los componentes lácteos naturales con variados efectos beneficiosos a la salud del consumidor (Rowan et al, 2005;Fitzgerald y Murria, 2006).…”
Section: Aditivos Lácteosunclassified
“…Salt is added to these cheeses as a preservative and taste enhancer [3]. Some physicochemical studies conducted on a variety of cheeses show that salt has a significant effect on rheological and textural aspects, useful lifetime, among others [4][5][6][7]. However, the World Health Organization (WHO) calls for the reduction of salt in foods, given the many diseases that may be developed if salt is consumed in excess [8].…”
Section: Introductionmentioning
confidence: 99%